A Tap and Gesture Hybrid Method for Authenticating Smartphone Users - Arif, Ahmed Sabbir; Pahud, Michel; Hinckley, Ken; Buxton, Bill (MobileHCI '13 Proceedings of the 15th international conference on Human-computer interaction with mobile devices and services, 2013)
This paper presents a new tap and gesture hybrid method for authenticating mobile device users. The new technique augments four simple gestures – up, down, left, and right, to the dominant digit lock technique, allowing users to either tap or perform any one of the four gestures on the digit keys. It offers in total 6,250,000 unique four-symbol password combinations, which is substantially more than the conventional techniques. Results of a pilot study showed that the new technique was slower and more error prone than the digit lock technique. However, we believe with practice it could get faster and more accurate. Also, most users were comfortable and all of them felt more secured while using the new technique.